Indian Ocean histories : the many worlds of Michael Naylor Pearson - Mukherjee, Rila; Seshan, Radhika (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Michael Naylor Pearson's work falls under the genre of global or world history and has tremendous impact on the study of the Indian Ocean world. He brought together different disciplines, and emphasized on the holistic view of the worlds of water. This book will serve as a guide and as a reader for Indian Ocean studies. It brings together scholars from different disciplines across the world (all of whom have been influenced by Michael Pearson's work) and points out several ways of writing the Indian Ocean history. The book discusses the changing nature of Indian Ocean history along with state and capital, regional identities, maritime networking, Islamic conversions, south Asian immigrants, Bay of Bengal linkages, East India Company, Indian seamen, the issues of colonial copyright, customs, excise and port cities etc. among many themes to give a comprehensive understanding of the study of Indian Ocean. With maritime history gaining prominence, this volume will be useful for scholars and researchers of history, modern history, medieval history, Indian history, colonial history and world history"--
Introduction: Indian Ocean histories / Rila Mukherjee -- The Indian Ocean : global nexus, 1500-1800 / Patrick Manning -- The Sodden archive : Africa, the Atlantic and the Indian Ocean / Isabel Hofmeyr -- The Kakatiyas, Motupalli and the Southern Bay of Bengal linkages / Radhika Seshan -- Regional identities, maritime networking and Islamic conversions in fifteenth-century Java / Kenneth R. Hall -- Brokers and go-betweens within the Portuguese state of India (1500-1700) / Amélia Polo'nia -- South Asian settlers at Batavia in the seventeenth and eighteenth centuries / Ryuto Shimada -- Physicians, surgeons, merchants and healers : production, circulation and reconfiguration of knowledge in eighteenth-century Portuguese India / Fabiano Bracht -- Indian seamen (lascars), shipboard labor regime, and the East India Company in the first half of the nineteenth century / Ghulam A. Nadri -- Hazards and history on the western Australian coast : the 'Pearling Fleet Disaster' of 1887 / Joseph Christensen -- Landscape, rajah and wax prints : contemporary archaeologies of India in Mozambique / Pedro Pombo -- Littoral shell tracks : tracing Burma's transregional pearl histories / Pedro Machado -- Michael Naylor Pearson : the discipline of history, the sea and the man / Rila Mukherjee.
Includes bibliographical references and index.
Keywords: Pearson, M. N. -- 1941-; Indian Ocean Region -- Historiography; Indian Ocean Region -- History